Diagnostic Performance of Ultrasound in Predicting the Extension of Disease in Advanced Ovarian Cancer - Asma Qamar Mudassir, Abdul Matin Qaisar, Sehrish Ahmad Ali, Wajiha Mehwish, Humaira Zulfiqar Saifee, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the diagnostic performance of ultrasound in predicting the extension of disease in advanced ovarian cancer. Study design: Prospective observational study. Place and duration of study: Department of Obstetrics & Gynaecology, Islam Teaching Hospital, Sialkot from 1st July 2020 to 30th June 2021. Methodology: Fifty-nine patients were enrolled and each patient underwent ultrasonography preoperatively and was assigned a six Fagotti-score. Surgical removal of ovarian mass was done through laparotomy. Midline incision was given. Peritoneal washings were taken for cytology. Omental biopsies were taken from various sites. Total abdominal hysterectomy was performed with bilateral oophorectomy. The ultrasound results and intraoperative extent of the ovarian malignancy spread were compared. The Cohen’s Kappa results were interpreted. Results: The mean age was 51.5±5.2 years. The range of Cohens Kappa was 0.7 in cases of carcinomatosis presented on the smaller/larger bowel. The predictive agreement value between the ultrasound and surgical cases for Cohens Kappa was 0.75 and 0.73 with mean as 0.74. Conclusion: The ultrasonography can be used as an important tool in identifying the advancement extent of ovarian cancer. Keywords: Ovarian cancer, Ultrasound, Cohen’s Kappa